(untitled) (Fiep Bulletin - online, 2011)
Introduction: The pregnancy is a time period that lasts about nine months, when the woman sleeps, protects and takes into her body another human being. Then the pregnant woman’s body goes through many changes involving several systems, including the respiratory one. It’s very important to understand the changes that happen on the physiology and mechanical ventilation of women during pregnancy. Objective: To measure the volume and lung capacity in normal pregnant woman from 28 to 38 weeks through pulmonary function test and comparing it to literature findings. Methodology: This research is characterized by a cross-sectional and quantitative study. The sample included ten young pregnant women in the age 18-30 years, primiparous and unigestas who are between 28th and 38th weeks pregnancy that had prenatal care with the gynecologist at the Health Unit of the November 14th District at Cascavel – PR. A questionnaire was applied and a pulmonary function test was performed: Spirometry according to the Brazilian Society of Thoracic standards and approved by the Ethics Committee. Results: The mean age was 25,7 years with 37,5 weeks of pregnancy and an average of eight prenatal visits. In relation to the symptoms during pregnancy, 33,3 % of women reported dyspnea, 20,0% tachycardia, 13,3% cough, 13,3% dizziness and 20,0% headache. Spirometry found the following: FVC: 2.87 ± 0.56 l / min, FEV1 2.60 ± 0.49 l / min, FEV1% 91.1 ± 7.60 l / min and 2.31 ± ETF 0.89 l / min which is consistent with values within the normal ranged when it’s compared to healthy adults. Conclusion: The symptoms with higher percentage were dyspnea and tachycardia which is not related to the spirometric test, even with all the physiological changes during this period, so it doesn’t reflect on the pregnancy results.